The boy to whom things happen: case report of a condition once named “Hysteria” - Rodrigues,Ana Rita (2020)
Abstract Introduction: Although banished from current mental disorders classifications, the condition formerly known as hysteria has clinical manifestations still puzzling to clinicians. Herein is briefly revised the historical concept of hysteria, as well as, psychological mechanisms underlying some of its current derivatives: conversive and dissociative disorders. Case report: A previously healthy 17-year-old boy presented with sudden onset of total strength loss in the lower limbs. After neurological assessment, the boy was diagnosed with conversion disorder. Two months later he developed trance and possession states requiring hospitalization, and later, dissociative amnesia. Despite psychological distress underlying patient’s symptoms, la belle indifference was also a meaningful issue. Discussion: This study presents a critical reflection about conversion and dissociative disorders and diagnostic challenges arising from their inconsistent and variable clinical features. Conclusion: With this case report, the authors intend to raise awareness to the risk of recurring care demand for care that can elicit iatrogenic harm and delayed proper treatment.